Pengaruh Penerapan Model Pembelajaran Problem Based Learning Terhadap Minat Dan Hasil Belajar Siswa Pada Mata Pelajaran Dasar Desain Komunikasi Visual - surya_anugrah saguh (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2025)
Abstract This study aims to investigate the effect of implementing the Problem Based Learning (PBL) model on students’ learning interest and achievement in the subject of Basic Visual Communication Design for Grade X DKV students at SMKN 5 Bungo. The research was motivated by the low level of student learning interest and achievement, many of which were still below the Learning Objective Achievement Criteria (KKTP), thereby requiring an innovative learning model that encourages active student engagement. The research employed an experimental method with a one group pretest-posttest design. The sample consisted of 15 students selected using saturated sampling. Research instruments included a questionnaire to measure learning interest and test items to assess learning achievement. Data were analyzed using normality tests, hypothesis testing with One Sample T-Test for learning interest, and Wilcoxon Signed Rank Test for learning achievement. The findings revealed that PBL had a significant effect on students’ learning interest, with a tcount of 45.616 exceeding ttable of 2.145 at a significance level of 0.000 < 0.05. Moreover, student achievement improved, as shown by an increase in the average score from 54.33 (pretest) to 74 (posttest) with a difference of 19.67, although the classical mastery level only reached 67%. Thus, the implementation of Problem Based Learning is proven to enhance students’ learning interest and achievement. Keywords: PBL, Learning Interest, Learning Achievement, Visual Communication Design